Multiprofessional action against viral hepatitis: an experience report (Research, Society and Development, 2021)
Viral hepatitis is a public health problem responsible for high rates of morbidity and mortality. In January 2019, Law No. 13,802 instituted the Yellow July, with the development of actions related to the prevention of viral hepatitis. The offer of rapid tests allows early detection of the viruses that cause hepatitis B and C and assistance to the patient. This is a descriptive study of the experience report type experienced by residents in Family Health, which occurred in the event “Multidisciplinary action against Viral Hepatitis", held in one of the bus stations in Cascavel, a city located in western Paraná. The high rates of HBV and HCV in the South region are noticeable, which justifies the actions developed by the residents since 211 tests for diagnosis of hepatitis B and C were administered. The activities proved to be an opportunity to raise awareness among the population, besides favoring the training of the residents involved as intermediates of health education and to provide a closer approach to the community. The residents’ action, through screening strategies, supports the health services and generates a better quality of life for the community.